Prediction of the Potential of Benzoxazinone, 2-phenyl-4H-benzo[1,3]oxazin-4-one, and 2-[2-(4-methoxyphenyl)vinyl]-3,1-benzoxazin-4-one as New Anti-Tuberculosis - Nofianti, Kholis Amalia; Hakim, Luqmanul; Suzana; Ifadotunikamah, Farida (Berkala Ilmiah Kimia Farmasi, 2024)
Even though it had been almost five decades, the decline in the prevalence of tuberculosis had still been low due to the rise of drug resistance. Recently, benzoxazinone compounds had begun to gain potential as anti-tuberculosis agents because of their interesting structure and similarity to isoniazid, the most widely used TB drug, which had reportedly experienced many cases of resistance. This research tested the ability of the core compound benzoxazinone and its two derivatives to bind to the enoyl ACP-CoA receptor, which was responsible for the formation of mycobacterial walls. In silico tests were carried out using pkcsm to determine the pharmacokinetic profile, and molecular docking tests using Molegro Virtual Docker were conducted to determine the pharmacodynamic profile through binding to the enoyl ACP-CoA receptor. The selected receptors were downloaded from the protein data bank with the code 2IDZ. The research results showed that the three test compounds had good intestinal and skin absorption profiles, indicating that they could be administered orally or transdermally. The docking results, expressed by moldock score and rerank score, showed that the three test compounds had better potential compared to isoniazid. Thus, the test compounds could be developed as new anti-tuberculosis agents. Keywords:  Tubercolosis, Benzoxazinone, Mycobacterium Tuberculosis, Pkcsm, Molegro Virtual Docker